Od „Hiszpanii imperialnej” do „imperium europejskiego”. Fundamentalne koncepcje ideowo-polityczne hiszpańskich narodowych rewolucjonistów przełomu XX i XXI w. Część II. Nacjonaliści europejscy - Karczewski, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article presents the system of fundamental principles and ideas promulgated by contemporary Spanish national-and-revolutionary parties. These organizations, from an ideological standpoint, can be placed within a general European doctrinal movement which came into existence in the sixties of the 20th century, called tercerism, the Third Way, the Third Position or revolutionary Nationalism. Spanish national-and-revolutionary parties base their conceptions on an outlook affirming modernity reason, science, progress and consider ancient civilizations of Greece and Rome the source of European identity. From the perspective of the system of ideas we can divide these parties into two groups, the first one being in favor of Spanish Nationalism Spanish nation as the highest value in the axiological system and the second one advocating European Nationalism the postulate of and the hope for the establishment of a new European nation and of a new European government. The article has been divided into two parts, respectively describing these ideological currents. In case of the parties supporting “European Nationalism” the system of ideas is based on the following pillars: Spanish peoples regions — Spain as the Fatherland — European nation. Spain is the necessary stage in building of a European nation and European Empire because the imperial idea was already implemented by the Spanish during the so-called Golden Age in the 16th century as the Spanish Monarchy. In the future the next form of the empire will be the European Empire as a nation-state, the creator and the depositary of which should exclusively be the European nation, integrating all peoples of Europe, not just Spain.
Keywords: narodowi rewolucjoniści; nacjonaliści europejscy; Hiszpania